Kriteria Penetapan Pailit Terhadap Notaris Sebagai Pejabat Umum Dan Notaris Sebagai Orang Pribadi Berdasarkan Asas Preferensi Hukum - Ariyanto; Lucky Suryo Wicaksono (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
A Notary in the provisions of Article 12 of the Notary Position Law can be dishonorably dismissed from his position if he is declared bankrupt based on a court decision that obtains permanent legal force. In the current regime of the Law on the Position of Notaries, there is no provision that explains regarding whether the purpose of bankruptcy of a Notary is a Notary in his or her capacity as a private person (person) or as a public official. The existence of a legal gap in determining bankruptcy criteria for notaries has raised various questions. This research uses a Normative Research typology which is supported by data obtained from secondary data sources in the form of primary legal materials and secondary legal materials. The conclusions of this research are, First, The bankruptcy of Notaries has been influenced by the blurred norm (vagenorm) created by Article 12 of the Law on the Position of Notaries. Second, the Bankruptcy Law and PKPU are enforced based on the legal preference principle of lex specialis derogate legi generali as the legal basis for resolving Notary bankruptcy issues.